ANALISIS KINERJA KEUANGAN PERUSAHAAN SUB-SEKTOR PROPERTY DAN REAL-ESTATE YANG TERCATAT DI BURSA EFEK INDONESIA 2018-2022 - Didi Rini Margasari; Candra Sigalingging (Journal Accounting International Mount Hope, 2024)
This research was conducted to measure the profitability and financial performance of property and real-estate sub-sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The main reason for this research is to provide an in-depth understanding of the efficient use of company capital and assets in generating profits. This research also aims to compare the financial performance between PT Alam Sutera Realty Tbk. and PT Agung Podomoro Land Tbk. by using profitability ratios such as Return on Equity (ROE), Return on Assets (ROA), Gross Profit Margin (GPM), and Net Profit Margin (NPM). Secondary data used in this research was obtained from audited annual reports. The analysis results show that PT Alam Sutera Realty Tbk. has a higher profitability ratio than PT Agung Podomoro Land Tbk., which indicates better efficiency in using company resources to generate profits.